Pathologies management of modern organization - E. Yu Pleshakova (Real Economics Publishing House, 2017)
The article presents an extended classification of pathology management system. The scale for assessing the level of pathological management is shown. The question of the interpretation of the results of assessing the level of pathological management is considered. The construction of pathological Profile Management is proposed to visually determine which diseases are pronounced. The results of studies of more than 300 domestic and foreign companies showed the most common pathologies of management in the practice, as well as the most pathological and without pathological organizations. It remains an open question about the reference values of pathological management, as well as the definition of the indicator and integrated approaches to the interpretation of quantifying.